The relationship between smoking dependence, exposure to cigarette smoke, carboxyhemoglobin and perioperative complications in patients who underwent laparoscopic cholecystectomy under general anesthesia - Eminoglu, Şermin; Ozgunay, Seyda Efsun (The European Research Journal, 2022)
Objectives: The aim of this study; to determine the effects of preoperative smoking dependence and noninvasively measured carboxyhemoglobin (COHb) levels on perioperative complications in patients who underwent elective laparoscopic cholecystectomy. Methods: Ninety patients (Group I: smoker, Group II: non-smoker, and Group III: passive smoker) who underwent laparoscopic cholecystectomy under general anesthesia were studied. The level of dependence of smokers was evaluated with the Fagerstrom Test for Nicotine Dependence (FNBT). Preoperative COHb level was determined with a pulse CO-oximeter by placing a sensor on the fingertip. Respiratory complications in the perioperative and recovery room and Modified Aldrete Score (MAS) in the recovery room were recorded as 5th, 10th and 15th min. Results: Female gender was significantly higher in Groups II and III. Significant increases were noted in Group I in terms of increased perioperative secretion and incidence of bronchospasm. In the recovery room, the increase in MAS 5th min in Group I and MAS 10th min and 15th min in Group III was significantly lower. In Group I, positive correlations between the COHb level and the number of cigarettes smoked and the FNBT level, and a negative correlation between MAS and the number of hours past after the last cigarette smoked were determined. In Group II, the COHb level correlated positively with the number of cigarette smokers at home and negatively with MAS. All these correlations were statistically significant. Conclusions: It was demonstrated that cigarette smoking increased the incidence of perioperative respiratory complications under general anesthesia. Preoperative COHb level estimated by the pulse CO-oximeter can be used as an indicant of the potential risk of perioperative repiratory complications.